A Conceptual Framework on the Role of Dynamic Pricing and eWOM in Online Transportation Services: The Jakarta Experience - Hermansyah Hermansyah; Usep Suhud; Setyo Ferry Wibowo (Greenation Research & Yayasan Global Resarch National, 2025)
This conceptual study aims to explore the influence of dynamic pricing and electronic word-of-mouth (eWOM) on consumer decisions in using online transportation services in Jakarta. By employing a Systematic Literature Review (SLR) approach, this research synthesizes findings from various academic sources to develop a theoretical framework integrating consumer behavior theories with pricing and digital communication strategies. The results suggest that dynamic pricing, while effective in optimizing operational efficiency, may trigger perceptions of price unfairness if implemented non-transparently—thereby undermining consumer trust and purchase intentions. Concurrently, eWOM is identified as a critical determinant that shapes consumer perceptions, brand trust, and service loyalty through reviews and ratings. The interplay between these two factors is particularly salient in Jakarta's competitive and digitally-driven transportation market. This framework is expected to provide a basis for future empirical studies and strategic guidance for service providers aiming to enhance customer satisfaction, loyalty, and sustainable competitive advantage.